KEY FACTORS INFLUENCING THE MANAGEMENT OF COOPETITION IN TERMS OF VALUE CREATION AND VALUE APPROPRIATION IN SMALL AND MEDIUM-SIZED ENTERPRISES - Vu, Thi Phuong Thao (My University, 2017)
Because there has been a significant increase in market competition, organizations tend to pursue the coopetitive relationships to expand the market presence and share the risks, particularly in the case of small and medium-sized companies. However, there is few empirical studies with the emphasis on the coopetition in small ventures. Therefore, the purpose of this research is to identify the factors that influence the value creation and appropriation within the coopetition and how these organizations manage such relationship in order to achieve the best outcome from their collaboration. In this study, three dominant theoretical areas including coopetition, value creation and value appropriation, and coopetition management approaches are discussed under two analysis levels: interfirm and intrafirm level. The empirical part of the current study relies on a qualitative case study of a coopetitive relationship between two Vietnamese SMEs. The current study suggests four elements that influence the value creation and value appropriation within the coopetition: market competition, the suitability in terms of resource system, protecting methods and management commitment. Then this paper highlights the significance of communication within the competing collaboration, whereas too straightforward protecting mechanisms lessen the commitment of the partner. In regards to coopetition management, it is revealed that partner selection should be focused at the beginning, while performance reviews should be maintained along the coopetition. Management commitment is considered above all to succeed in collaborating with competitors.
Keywords: coopetition in SMEs; value creation and value appropriation; coopetition management; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|